Die Horizonte der Gemeindekonflikte in den Sendschreiben der Johannesoffenbarung - Koch, Stefan 1965- (2017)
The seven letters of the Book of Revelation (Apc 2-3) deal with different situations. Only some of them represent actual dangers, some try to give warnings for future challenges, others look back on difficult times that already belong to the past. But these letters have also something in common: they speak indistinctively about a group called the 'Nicolaites', the people of a certain 'Jezebel', and a group belonging to some 'Balaam'. The essay deals with the question whether these groups are real, actual or traditional. It tries to argue that they are looked at from the viewpoint of scripture and from traditional Noahite rules (or some of them, which are found in Act 15). The writer of the letters therefore pledges to stick by these rules. And the Book of Revelation itself might be reconsidered as a living part of their 'Wirkungsgeschichte'